Development of Group Counseling Guideline using Modeling Technique to Enhance Self-Management - Loban , Maria Natalia; Naisanu , Merita Florawati; Solle , Lebrina (COUNS-EDU: The International Journal of Counseling and Education, 2024)
This research aims to produce a group counseling guideline using modeling technique to improve self-management. The method used in this research is the research and development method. This guidelines was validated by two expert validators with a background in guidance and counseling and languages, as well as by one practitioner validator with a background in guidance and counseling education. The sampling technique used was purposive sampling which was adapted to the research objectives. The number of samples in this study was 5 people, adjusted to the number of counseling group members, namely 2-8 people. Group counseling using modeling techniques to improve self-management consists of seven counseling sessions. Each session in group counseling uses modeling techniques with live models and symbolic models. Each group counseling session is directed to achieve indicators in self-management namely self motivation, self organization, self control, self development.